Introduction to “Implementations of two-dimensional liquidchromatography” by G. Guiochon, N. Marchetti, K. Mriziq,R.A. Shaliker [J. Chromatogr. A 1189 (2008) 109–168] - Jandera, Pavel (My University, 2016)
It is great pleasure and honor for me to introduce this reviewpaper by Georges Guiochon et al. There is nobody who could matchGeorges in the fundamental theoretical knowledge of physico-chemical principles covering all fields of analytical separations,including gas, planar and column liquid and supercritical fluid chro-matography techniques. The plethora of his papers amounting toincredible 1136, cited so far almost 30,000 times (according to Webof Science), had and still has enormous impact on the developmentin all areas of separation sciences. This is very well demonstrated bythe present review of multi-dimensional liquid chromatography,published by Georges and his co-workers in 2008.
Úvod do "Implementace dvourozměrné kapalinové chromatografie" G. Guiochon, N. Marchetti, K. Mriziq, R.A. Shaliker [J. Chromatogr. 1189 (2008) 109-168]
Keywords: two-dimensional liquidchromatography; Introduction; Guiochon; Shaliker; dvou-dimenzionální kapalinová chromatografie; úvod; Guiochon; Shaliker